Analysis of Conversation Implicatur in Youtube Channel Speech "Indonesian Comedy Film" Edition "Doa Cari Jodoh" - Roni Mainata Alam; Moh Irfan firjatullah (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
Implicatures in the speech of the Indonesian comedy film YouTube channel edition of Doa Cari Jodoh. The purpose of this study is to provide an overview and describe the types of implicatures and violations of maxims in the speech of the Indonesian Comedy film edition of Doa Cari Jodoh. The approach used in this study is the Qualitative Descriptive approach, the data source in this study is a video found on the Indonesian comedy film YouTube channel edition of "Doa Cari Jodoh". The research data is in the form of excerpts of speech delivered by characters that are categorized in the form of conversational implicatures and violations of the principle of cooperation. The methods used are the listening method, observation techniques, and note-taking techniques. The results of the study found several data that include types of conversational and speech implicatures that violate maxims. There are 5 data that include types of implicatures, namely, 2 types of general implicatures, 2 types of scale implicatures, and 1 type of special implicature. And found 3 data Violation of the maxim of quantity, 4 violations of the maxim of quality, 1 violation of the maxim of relevance/relationship, and 1 violation of the maxim of manner.